EXERCISE HABITS OF HEALTH CARE PROFESSIONAL STUDENTS AND NON HEALTH CARE PROFESSIONAL STUDENTS- A CROSS SECTIONAL SURVEY - JAGATHEESAN ALAGESAN; VIVEK PANDEY (International Journal of Pharma and Bio Sciences, 2014)
Exercise is an important component of healthy lifestyle to reduce a person’s risk of developing the disease and subsequent disability. Health care professional students’ physical activity behaviours may provide an indicator for the future of physical activity among those in the profession. This study compared the exercise habits of health care professional students and non-health care professional students. A cross sectional survey was done among the health care professional and non-health care professional students of Saveetha University, Chennai to find out exercise habits through questionnaire. A total of 1274 subjects participated in the study with the Mean ± SD age of 19.81±1.84 years. Exercise habits were analysed under three categories namely vigorous exercises, moderate exercises and strength training. There were no significant difference between health care professional students and non-health care professional students in exercise habits with p value more than 0.05. This study concludes that the health care professional students exercised at the same levels that are of non-health care professional students.